PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA, GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP KINERJA DOSEN - MEITHIANA INDRASARI; NUR SYAMSUDIN; BAMBANG RADITYA PURNOMO; EDDY YUNUS (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2018)
The Tridharma as the duty of lecturer, which is to do teaching, research and community service. Some factors that influence the performance of lecturers are organizational culture, work environment, leadership style, and job satisfaction. Therefore, this study aims to examine the influence of organizational culture, work environment, leadership style to lecturer's job satisfaction and analyze the influence of organizational culture, work environment, leadership style to lecturer's performance. This study took 64 samples through census method, and the data collected through research questionnaire in the form likert scale. The result of hypothesis proof analysis shows that organizational culture, work environment, leadership style have positive and significant effect to job satisfaction of lecturer of Bojonegoro State Community Academy. As well as organizational culture, work environment, leadership style, job satisfaction has a positive and significant impact on the performance of lecturers of Bojonegoro State Community Academy. It is suggested to the community academy managers that the lecturer's performance can be optimal, to give stimulation to the lecturers to work in education through awards, to increase salary, to maintain relationships, to create healthy competition, to appraise fair performance, from the academy. Encourage continuing education to a higher level. Motivate to undertake research and community service relevant to the field at the expense of the institution / academy or grant.